Modulation of nucleus accumbens connectivity by alcohol drinking and naltrexone in alcohol-preferring rats: a manganese-enhanced magnetic resonance imaging study - Dudek, Mateusz; Sommer, Wolfgang H. (European neuropsychopharmacology, 2016)
The nonselective opioid receptor antagonist naltrexone is now used for the treatment of alcoholism, yet naltrexone׳s central mechanism of action remains poorly understood. One line of evidence suggests that opioid antagonists regulate alcohol drinking through interaction with the mesolimbic dopamine system. Hence, our goal here was to examine the role of the nucleus accumbens connectivity in alcohol reinforcement and naltrexone׳s actions using manganese-enhanced magnetic resonance imaging (MEMRI). Following long-term free-choice drinking of alcohol and water, AA (Alko Alcohol) rats received injections of MnCl2 into the nucleus accumbens for activity-dependent tracing of accumbal connections. Immediately after the accumbal injections, rats were imaged using MEMRI, and then allowed to drink either alcohol or water for the next 24h. Naltrexone was administered prior to the active dark period, and the second MEMRI was performed 24h after the first scan. Comparison of signal intensity at 1 and 24h after accumbal MnCl2 injections revealed an ipsilateral continuum through the ventral pallidum, bed nucleus of the stria terminalis, globus pallidus, and lateral hypothalamus to the substantia nigra and ventral tegmental area. Activation was also seen in the rostral part of the insular cortex and regions of the prefrontal cortex. Alcohol drinking resulted in enhanced activation of these connections, whereas naltrexone suppressed alcohol-induced activity. These data support the involvement of the accumbal connections in alcohol reinforcement and mediation of naltrexone׳s suppressive effects on alcohol drinking through their deactivation.